East-facing Jangha (wall) of the Mahanaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
East-facing jangha (wall) of the Mahanaleshwar Temple is similar in scheme to the details on the north-facing one. The bhadra (central projection) has a Natesha icon, the slender intermediary projections have surasundaris (celestial damsels) and the corner projections have dikapalas (gods of cardinal directions). Each of these projections of the jangha has four kapotali (cyma recta) like mouldings above them and similar slender horizontal mouldings below. The difference is the stone material of the intermediary and corner projections is noteworthy.